Governmental venture capital in Europe: Screening and certification - Guerini, Massimiliano; Quas, Anita (Journal of Business Venturing, 2016)
This paper investigates the screening and certification abilities of government-managed venture capital (GVC) firms in Europe. Using a sample of European high-tech entrepreneurial companies, we show that GVC funding increases the likelihood that companies will receive private venture capital (PVC). Moreover, GVC-funded companies that have received a first round of PVC are at least as likely as other PVC-backed companies to receive a second round of PVC or to be listed or acquired. After ruling out alternative explanations, we interpret these results as positive evidence of GVC firms' abilities in selecting promising companies and certifying them to PVC investors.